The impact of childhood emotional abuse on non-suicidal self-injury in adolescents with mood disorders: a moderated mediation model - Wang, Lianzi; Zha, Guifang; Chen, Fangfang; Zhang, Jingyan; Li, Xiaoyue; Wang, Ziliang; Luo, Jia; Song, Chuanfu (Frontiers in Psychiatry, 2025)
ObjectivesThis study aims to identify factors associated with NSSI severity in adolescents with mood disorders and examine the mediating role of emotional expression difficulties and the moderating role of bullying in the relationship between childhood emotional abuse and NSSI.MethodsUsing a convenience sampling method, 242 adolescents with mood disorders were surveyed with the Adolescent Self-Harm Questionnaire, Childhood Abuse Questionnaire, Toronto Alexithymia Scale, and Beck Suicidal Ideation Scale. Stepwise linear regression was performed to examine associations between NSSI severity and key predictors, including childhood trauma subtypes, alexithymia, and bullying history. The mediation and moderation effects were tested using the Hayes Process plugin.ResultsThe prevalence of NSSI among adolescents with mood disorders was 81.40% (n = 197). Experiences of bullying (β=0.19, P=0.001), childhood emotional abuse (β=0.25, P<0.001), and difficulties in emotional expression (β=0.25, P<0.001) were positively correlated with the severity of NSSI, while age (β=-0.12, P=0.046) was negatively correlated. Difficulties in emotional expression partially mediated the relationship between childhood emotional abuse and NSSI, with a mediation effect size of 0.25, Bootstrap 95% CI (0.02–0.10), accounting for 21% of the total effect. This mediation effect was moderated by experiences of bullying, showing a positive association between the severity of NSSI and the interaction term of emotional expression difficulties and bullying (β=3.23, P<0.001), with a moderated mediation index of 0.48 and Bootstrap 95% CI (0.08–1.14).ConclusionChildhood emotional abuse in adolescents with mood disorders can have both direct and indirect effects on NSSI through difficulties in emotional expression, and experiences of bullying moderate the relationship between NSSI and emotional expression difficulties.